Normal modes of a small gamelan gong - Robert, Perrin; Daniel, P. Elford; Luke, Chalmers; Gerry, M. Swallowe; Thomas, R. Moore; Sinin, Hamdan; Benjamin, J. Halkon (Acoustical Society of America, 2014)
Studies have been made of the normal modes of a 20.7 cm diameter steel gamelan gong. A finite-element model has been constructed and its predictions for normal modes compared with experimental results obtained using electronic speckle pattern interferometry. Agreement was reasonable in view of the lack of precision in the manufacture of the instrument. The results agree with expectations for an axially symmetric system subject to small symmetry breaking. The extent to which the results obey Chladni's law is discussed. Comparison with vibrational and acoustical spectra enabled the identification of the small number of modes responsible for the sound output when played normally. Evidence of non-linear behavior was found, mainly in the form of subharmonics of true modes. Experiments using scanning laser Doppler vibrometry gave satisfactory agreement with the other methods.